2019
DOI: 10.17675/2305-6894-2019-8-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion control of Cu–Ni alloy in hydrochloric acid by amines compounds

Abstract: Inhibitors of corrosion are chemicals materials that, when added in little amount to an environment impede the development of corrosion reactions. The inhibitors use is represent one of selections of protecting alloys of metals from corrosion, which leads to protect surfaces of metal in corrosive environments. Most organic compounds inhibitors that contain nitrogen, are effective inhibitors in the acidic medium, especially hydrochloric acid. Copper represents noble metal and requiring very strong oxidants for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In previous studies, the use of various nitrogen compounds has been reported, among others are oligomers of 4-vinylpry dine (Ilim et al, 2021b;Ilim et al, 2016e), oligomer of 2vinylpyridine (Ilim et al, 2021d) , oligomer of 4-vinylpiperidine (Ilim et al, 2017c) , and ethylenediamine and tetraethylenepentamine (Mahmmod et al, 2019) . In the context of nitrogen compounds preparation, other potential raw materials are vegetable oils, considering their availability, renewability, biodegradability, and non-toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the use of various nitrogen compounds has been reported, among others are oligomers of 4-vinylpry dine (Ilim et al, 2021b;Ilim et al, 2016e), oligomer of 2vinylpyridine (Ilim et al, 2021d) , oligomer of 4-vinylpiperidine (Ilim et al, 2017c) , and ethylenediamine and tetraethylenepentamine (Mahmmod et al, 2019) . In the context of nitrogen compounds preparation, other potential raw materials are vegetable oils, considering their availability, renewability, biodegradability, and non-toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The profound process playing an active part in industry is corrosion, especially for alloys and metals. There are wide applications for mild or carbon steel in industries and petroleum applications, such as flow lines and down hole tubular [1][2][3][4][5][6][7][8][9]. Inhibitors of corrosion process represent enormous practical emphasis, being comprehensive employed in minimizing metallic waste and the inhibitor use is represent one of the best methods known of corrosion protection process in industrial field and the best way to resist corrosion growth [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%